The impact of air quality on tourism: a systematic literature review. Issue 1 (27th March 2020) - Eusébio, Celeste; Carneiro, Maria João; Madaleno, Mara; Robaina, Margarita; Rodrigues, Vítor; Russo, Michael; Relvas, Hélder; Gama, Carla; Lopes, Myriam; Seixas, Vania; Borrego, Carlos; Monteiro, Alexandra
Abstract : Purpose: Tourism may have important positive and negative economic, socio-cultural and environmental impacts. However, cultural and natural resources are also the base to the development of competitive destinations and changes in these resources can have an important impact on tourism development. Despite the considerable literature regarding the impacts of tourism, a limited number of studies examine the impact of the environment on tourism, specifically the impact of air quality (AQ). Therefore, this paper aims to review what is known about the impact of AQ on tourism demand, analysing the different methods and approaches used, as well as the results obtained. Design/methodology/approach: A systematic literature review method was used to examine the state of the art in this topic and identify research gaps and new research directions. Only 26 papers were identified that examine the impact of AQ on tourism demand. Findings: The majority of the studies were carried out in China and investigate the impact of AQ on tourism from the perspective of tourism demand. Both global (tourism demand) and individual (tourist perceptions) approaches have been used to investigate the impact of AQ on tourism. Originality/value: This is the first systematic literature review on the impact of outdoor AQ on tourism demand. Moreover, this paper analyses the methods and approaches that have been used in the literature to examine the impact of outdoor AQ on tourism demand. The paper ends with a discussion on the identified research gaps concerning the influence of AQ on tourism development.